Pengembangan Bahan Ajar Pengantar Hukum Bisnis Dengan Pendekatan Dialog Kreatif Partisipatori (Integralistik, 2021)
The aim of this research is; (1) to determine the process of developing and producing teaching materials for introducing business law with a participatory creative dialogue approach; (2) to determine the feasibility of introductory business law teaching materials using a participatory creative dialogue approach. The research and development (R D) method was used in this research with stages, namely (1) initial investigation and design, (2) realization, (3) testing, and (4) descriptive-qualitative analysis to determine the feasibility of the resulting teaching materials. both in material, content / substance, language, appearance, user friendly for lecturers and students. The results of the assessment of the feasibility of teaching materials developed were assessed by students,Â lecturers and experts with indicators of accuracy of content assessment, accuracy of content coverage, digestibility, language use, compulsion, illustrations, completeness of the components showing an average score of 3.68 or very good category. Thus the teaching materials developed are very good for use in introductory business law courses or can be used as a relevant reference source in introductory business law courses.